Analisis Total Quality Management Pada UMKM Sinar Laut di Kabupaten Bandung - Luthfiah Al Afifah; Junianto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The food industry is growing in line with increasing consumer demand for high quality products. One of the products in demand is fish balls, which have a high nutritional value and are an important source of animal protein. This study focuses on Sinar Laut brand fish balls, which are popular processed products among consumers. In order to maintain product quality and competitiveness, the implementation of Total Quality Management (TQM) is very important. TQM is a management approach that aims for continuous improvement at every stage of production. This study aims to analyse the implementation of TQM in Sinar Laut fish balls. The method used is descriptive, with data collected through direct observation of the production process and interviews with business owners. The results of the study indicate that Sinar Laut has implemented TQM principles such as continuous improvement, active employee participation and strong leadership in its production process.